Engineered IRES-mediated promoter-free insulin-producing cells reverse hyperglycemia - Li, Yumin; Ahamed Younis, Doulathunnisa; He, Cong; Ni, Chengming; Liu, Rui; Zhou, Yunting; Sun, Zilin; Lin, Hao; Xiao, Zhongdang; Sun, Bo (Frontiers in Endocrinology, 2024)
Background Endogenous insulin supplementation is essential for individuals with type 1 diabetes (T1D). However, current treatments, including pancreas transplantation, insulin injections, and oral medications, have significant limitations. The development of engineered cells that can secrete endogenous insulin offers a promising new therapeutic strategy for type 1 diabetes (T1D). This approach could potentially circumvent autoimmune responses associated with the transplantation of differentiated β-cells or systemic delivery of viral vectors. Methods We utilized CRISPR/Cas9 gene editing coupled with homology-directed repair (HDR) to precisely integrate a promoter-free EMCVIRES-insulin cassette into the 3’ untranslated region (UTR) of the GAPDH gene in human HEK-293T cells. Subsequently quantified insulin expression levels in these engineered cells, the viability and functionality of the engineered cells when seeded on different cell vectors (GelMA and Cytopore I) were also assessed. Finally, we investigated the therapeutic potential of EMCVIRES-based insulin secretion circuits in reversing Hyperglycaemia in T1D mice. Result Our results demonstrate that HDR-mediated gene editing successfully integrated the IRES-insulin loop into the genome of HEK-293T cells, a non-endocrine cell line, enabling the expression of human-derived insulin. Furthermore, Cytopore I microcarriers facilitated cell attachment and proliferation during in vitro culture and enhanced cell survival post-transplantation. Transplantation of these cell-laden microcarriers into mice led to the development of a stable, fat-encapsulated structure. This structure exhibited the expression of the platelet-endothelial cell adhesion molecule CD31, and no significant immune rejection was observed throughout the experiment. Diabetic mice that received the cell carriers reversed hyperglycemia, and blood glucose fluctuations under simulated feeding stimuli were very similar to those of healthy mice. Conclusion In summary, our study demonstrates that Cytopore I microcarriers are biocompatible and promote long-term cell survival in vivo. The promoter-free EMCVIRES-insulin loop enables non-endocrine cells to secrete mature insulin, leading to a rapid reduction in glucose levels. We have presented a novel promoter-free genetic engineering strategy for insulin secretion and proposed an efficient cell transplantation method. Our findings suggest the potential to expand the range of cell sources available for the treatment of diabetes, offering new avenues for therapeutic interventions.